Impact of a quality improvement programme on the preparation and administration of medications via a nasoenteral feeding tube: 2014–2019 intervention study - Fernanda Raphael Escobar Gimenes; Rosana Aparecida Pereira; Fabiana Bolela de Souza; Mayara Carvalho Godinho Rigobello; Laís Rosa Moreno da Costa; Carlos Alberto Grespan Bonacim; Marcia Mazzeo Grande (BMJ Open Quality)
Aims Evaluate the impact of a quality improvement programme on the reduction of feeding tube obstruction frequencies, analyse the predictive variables of this safety incident, and estimate the economic costs related to the quality improvement programme during the period from 2014 to 2019.Methods Plan–Do–Study–Act cycles were performed to test the changes in drug preparation and administration processes via a nasoenteral feeding tube and to evaluate the outcome, process and balance measures. Statistical control charts were elaborated, and the bottom-up direct costing methodology was used to estimate the costs of the improvement programme. The impact of the programme on the monitoring measures was evaluated using logistic regression analysis.Interventions The following changes were tested in the hospital participating in the study: acquisition of the Easy Crush equipment for tablet crushing, use of appropriate packaging to crush hard tablets, standardise procedures for scheduling administration times and/or substitution of the pharmaceutical form, educational activities for the nursing team and elaboration and availability of infographics for the nursing team, patients and/or family/caregivers.Results There was a significant improvement in the frequency of tube obstructions, from 41.1% in 2014 to 57.9% in 2015–2017 and 9.6% in 2018–2019 (p=0.0010). After the execution of the improvement programme, it was estimated that the cost of dose preparation was reduced from R$1067.50 in 2014 to R$719.80 in 2015–2017 and R$433.10 in 2015–2019.Conclusion By re-establishing the processes of drug preparation and administration via a nasoenteral feeding tube, through the acquisition of appropriate equipment for crushing hard tablets, together with educational activities for the nursing team, we could observe a reduction in tube obstructions and the cost of processes.